Comparative Evaluation of Actual and Planned Productivity of the Samarinda City Police Dormitory Construction Project Workforce - Herwin Wahyudi; Risma Marleno; Erni Puspanantasari Putri (LPPM of NAROTAMA UNIVERSITY, 2026)
This study aims to evaluate the comparison between actual and planned labor productivity in the Police Housing Construction Project in Samarinda as a basis for assessing construction efficiency. Actual productivity data were obtained from field observations, daily reports, and measurement of work volume and duration. Planned productivity was calculated using the Unit Price Analysis (AHS), project scheduling, and manpower planning. The results show significant differences between actual and planned productivity in various work categories. Actual structural productivity ranges from 0.71 to 1.20 m³/day, which is lower than the planned productivity of 1.456–3.21 m³/day. Finishing works also display substantial deviation, with actual productivity of 27.52–80 m²/day compared to the planned 44–135 m²/day. These discrepancies result in slower progress, increased risk of project delays, and reduced time management efficiency. Key factors contributing to productivity gaps include field conditions, weather disturbances, material mobilization, worker experience, and coordination effectiveness among subcontractors. The findings highlight the importance of periodic productivity control and improved field management to meet planned targets.